2008
DOI: 10.3138/cmlr.64.4.605
|View full text |Cite
|
Sign up to set email alerts
|

Peer–Peer Interaction between L2 Learners of Different Proficiency Levels: Their Interactions and Reflections

Abstract: This study draws on sociocultural theory to explore how adult ESL learners interact with either a higher- or a lower-proficiency peer during pair problem solving, and how they each perceive the interactions with their partners. Three ESL learners engaged in a three-stage task: pair writing; pair noticing; and individual writing with two learners, one with a higher and one with a lower L2 proficiency level than their own. These three learners engaged in stimulated recall sessions and were interviewed after all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 35 publications
4
68
1
5
Order By: Relevance
“…Plusieurs chercheurs en didactique de l'écriture ont examiné les effets de la rétroac-tion verbale des pairs en langue première et seconde, tant chez les enfants que chez les adultes (Beer-Toker, Huel et Richer, 1991 ;Blain, 2001 ;Blain et Painchaud, 1999 ;Brakel-Olson, 1990 ;Connor et Asenavage, 1994 ;Gere et Stevens, 1985 ;Harris, Graham et Mason, 2006 ;Mendonça et Johnson, 1994 ;Nelson et Murphy, 1993 ;Samway, 1987 ;Storch, 2005 ;Urzùa, 1987 ;Watanabe, 2008).…”
Section: Effets De La Rétroaction Verbale Des Pairsunclassified
See 1 more Smart Citation
“…Plusieurs chercheurs en didactique de l'écriture ont examiné les effets de la rétroac-tion verbale des pairs en langue première et seconde, tant chez les enfants que chez les adultes (Beer-Toker, Huel et Richer, 1991 ;Blain, 2001 ;Blain et Painchaud, 1999 ;Brakel-Olson, 1990 ;Connor et Asenavage, 1994 ;Gere et Stevens, 1985 ;Harris, Graham et Mason, 2006 ;Mendonça et Johnson, 1994 ;Nelson et Murphy, 1993 ;Samway, 1987 ;Storch, 2005 ;Urzùa, 1987 ;Watanabe, 2008).…”
Section: Effets De La Rétroaction Verbale Des Pairsunclassified
“…En effet, certains scripteurs semblent, à la suite des révisions, être plus à même de faire des changements grammaticaux dans leurs compositions, ce qui mène à une amélioration (Villamil et De Guerrero, 1998). Généralement, les scripteurs adoptent aussi une attitude positive face à la rétroaction verbale de leurs pairs (Bell, 1991 ;Mendonça et Johnson, 1994), quel que soit leur niveau de compétence en langue (Storch, 2005 ;Watanabe, 2008), quoique certains puissent préférer la rétroaction de l'enseignant (Nelson et Carson, 1998). Plus récemment, les approches en enseignement de l'écriture privilégient l'intégration des interactions entre les pairs pour favoriser l'apprentissage des stratégies de gestion du processus, tant pour l'apprentissage de l'écriture en milieu majoritaire ( Bien que le groupe de révision rédactionnelle soit un dispositif didactique de plus en plus populaire, aucune étude n'a permis de vérifier quels types de commentaires sont intégrés ni pourquoi le scripteur en tient compte.…”
Section: Effets De La Rétroaction Verbale Des Pairsunclassified
“…She found that although these studies did show that learners were able to do so in peer interaction, there was no sign that their interaction led to effective acquisition of grammatical structure. Watanabe (2008) and Watanabe and Swain (2007) investigated whether learners' proficiency level had an impact on their production of language-related episodes and on their post-test performance. They found that collaborative patterns among learners had more of an impact on both measurements than did learners' proficiency level.…”
Section: Peer Interaction Researchmentioning
confidence: 99%
“…Among researchers from an array of paradigms, it is seen as a useful component to L2 classroom learning, particularly when learners do not have frequent access to native speakers of their L2 (Pica, 1996;Watanabe, 2008). Researchers working within the interactionist paradigm have long held that L2 interaction between language learners is superior for L2 learning because, in comparison with their behavior when interacting with native speakers, learner-learner interaction is characterized by more production, a greater amount of communication breakdowns and negotiation for meaning, a wider variety of sociolinguistic functions, less learner anxiety, more motivation, and the presence of more input modification, which is thought to be conducive to L2…”
Section: Peer Interaction Researchmentioning
confidence: 99%
“…It is noteworthy that although students may usually be paired with classmates of similar or different proficiency levels in a L2 writing class, the research investigating the impact of proficiency-pairing in L2 writing remains scant, and most of the research on peer dyads in either L2 writing or language learning in general mainly focused on the process of peer interactions, with little attention paid to the effects of those interactions on students' subsequent draft revisions (e.g., Leeser, 2004;Lockhart & Ng, 1995;Nelson & Murphy, 1993;Storch, 1998Storch, , 2002aStorch, , 2002bStorch, , 2005aStorch, , 2005bStorch, , 2007aStorch, , 2007bStorch & Aldosari, 2013;Watanabe, 2008;Watanabe & Swain, 2007). Earlier studies like Lockhart and Ng (1995), Nelson and Murphy (1993), and Storch (2002a) examined the types of student interactions that were likely to result in students' incorporation of a higher percentage of peer response into their draft revisions.…”
Section: Literature Reviewmentioning
confidence: 99%